2014
DOI: 10.1051/0004-6361/201322779
|View full text |Cite
|
Sign up to set email alerts
|

Seismic constraints on the radial dependence of the internal rotation profiles of sixKeplersubgiants and young red giants

Abstract: Context. We still do not understand which physical mechanisms are responsible for the transport of angular momentum inside stars. The recent detection of mixed modes that contain the clear signature of rotation in the spectra of Kepler subgiants and red giants gives us the opportunity to make progress on this question. Aims. Our aim is to probe the radial dependence of the rotation profiles for a sample of Kepler targets. For this purpose, subgiants and early red giants are particularly interesting targets bec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
458
3
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 358 publications
(497 citation statements)
references
References 93 publications
35
458
3
1
Order By: Relevance
“…Several asteroseismic studies (Beck et al 2012;Mosser et al 2012;Deheuvels et al 2014Deheuvels et al , 2015Di Mauro et al 2016) have measured the core rotation rates of RGB/clump stars. The relatively slow core rotation rates indicate that strong angular momentum transport mechanisms are at work (Cantiello et al 2014), coupling the radiative cores with the convective envelope.…”
Section: Angular Momentum Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Several asteroseismic studies (Beck et al 2012;Mosser et al 2012;Deheuvels et al 2014Deheuvels et al , 2015Di Mauro et al 2016) have measured the core rotation rates of RGB/clump stars. The relatively slow core rotation rates indicate that strong angular momentum transport mechanisms are at work (Cantiello et al 2014), coupling the radiative cores with the convective envelope.…”
Section: Angular Momentum Transportmentioning
confidence: 99%
“…This technique utilizes observations of mixed modes, oscillations that behave as pressure waves (p-modes) near the stellar surface and gravity waves (g-modes) in the stellar core (Scuflaire 1974;Osaki 1975;Aizenman et al 1977;Dziembowski et al 2001;Christensen-Dalsgaard 2004;Dupret et al 2009). Mixed modes have been used successfully to determine the evolutionary status of red giant stars Stello et al 2013;Mosser et al 2014), and to measure their internal rotation rate (Beck et al 2012;Mosser et al 2012;Deheuvels et al 2014Deheuvels et al , 2015. Turbulent convection in the red giant envelope excites these modes, with part of the wave energy leaking through the evanescent region into the gmode cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of rotational splittings of mixed modes (Beck et al 2012;Deheuvels et al 2012;Mosser et al 2012) has given direct insight into the internal rotation of red giants and their variations with evolution. In the subgiant phase, Deheuvels et al (2014) showed that the core spins up and the envelope spins A&A 605, A75 (2017) down. This was qualitatively expected, considering that the deepest layers below the H-burning shell contract, while the layers above expand.…”
Section: Introductionmentioning
confidence: 99%
“…The splitting of mixed modes show that red-giant cores rotate faster than their convective envelope (Beck et al 2012;Deheuvels et al 2012) and opens up the possibility of probing their internal rotation rates (Deheuvels et al 2014(Deheuvels et al , 2015Di Mauro et al 2016). In fact, for our target stars Corsaro et al (2015a) determined the frequencies of many mixed dipolar A&A 591, A99 (2016) KIC ∆ν ν max T eff log g Z/X 3744043 A 9.90 ± 0.05 112.5 ± 0.2 4906 ± 91 3.05 ± 0.11 −0.37 ± 0.04 6117517 B 10.16 ± 0.05 120.3 ± 0.2 4734 ± 91 3.01 ± 0.11 0.38 ± 0.03 6144777 C 11.01 ± 0.06 129.7 ± 0.2 4788 ± 91 3.07 ± 0.11 0.24 ± 0.03 7060732 D 10.94 ± 0.05 132.3 ± 0.2 4892 ± 200 − − 7619745 E 13.13 ± 0.07 170.8 ± 0.2 4932 ± 91 3.13 ± 0.11 −0.04 ± 0.03 8366239 F 13.70 ± 0.07 185.6 ± 0.4 4948 ± 91 3.10 ± 0.11 −0.00 ± 0.03 8475025 G 9.66 ± 0.05 112.9 ± 0.3 4854 ± 91 3.01 ± 0.11 −0.04 ± 0.03 8718745 H 11.40 ± 0.06 129.3 ± 0.2 4769 ± 91 2.94 ± 0.11 −0.32 ± 0.04 9145955 I 11.00 ± 0.06 131.7 ± 0.2 4925 ± 91 3.04 ± 0.11 −0.32 ± 0.03 9267654 J 10.34 ± 0.05 118.6 ± 0.2 4824 ± 91 3.22 ± 0.11 −0.04 ± 0.03 9475697 K 9.88 ± 0.05 115.1 ± 0.2 4791 ± 91 2.90 ± 0.11 0.19 ± 0.03 9882316 L 13.78 ± 0.07 182.0 ± 0.5 5093 ± 91 3.20 ± 0.11 −0.41 ± 0.04 10123207 M 13.67 ± 0.07 160.9 ± 0.2 4840 ± 91 2.98 ± 0.11 −0.45 ± 0.04 10200377 N 12.47 ± 0.06 142.5 ± 0.2 4828 ± 91 3.00 ± 0.11 −0.63 ± 0.04 10257278 O 12.20 ± 0.06 149.5 ± 0.3 4887 ± 91 2.99 ± 0.11 0.06 ± 0.03 11353313 P 10.76 ± 0.05 126.5 ± 0.2 4955 ± 91 3.01 ± 0.11 −0.42 ± 0.04 11913545 Q 10.18 ± 0.05 117.1 ± 0.2 4960 ± 200 − − 11968334 R 11.41 ± 0.06 141.4 ± 0.3 4826 ± 91 3.10 ± 0.11 0.35 ± 0.03 12008916 S 12.90 ± 0.06 161.9 ± 0.3 5107 ± 200 − −…”
Section: Introductionmentioning
confidence: 99%